Evidence of Phytotoxicity and Genotoxicity in Hordeum vulgare L. Exposed to CeO2 and TiO2 Nanoparticles - Mattiello, Alessandro; Filippi, Antonio; Pošćić, Filip; Musetti, Rita; Salvatici, Maria C.; Giordano, Cristiana; Vischi, Massimo; Bertolini, Alberto; Marchiol, Luca (Frontiers in Plant Science, 2015)
Engineered nanoscale materials (ENMs) are considered emerging contaminants since they are perceived as a potential threat to the environment and the human health. The reactions of living organisms when exposed to metal nanoparticles (NPs) or NPs of different size are not well known. Very few studies on NPs-plant interactions have been published, so far. For this reason there is also great concern regarding the potential NPs impact to food safety. Early genotoxic and phytotoxic effects of cerium oxide nanoparticles (nCeO2) and titanium dioxide nanoparticles (nTiO2) were investigated in seedlings of Hordeum vulgare L. Caryopses were exposed to an aqueous dispersion of nCeO2 and nTiO2 at respectively 0, 500, 1000 and 2000 mg l-1 for 7 days. Genotoxicity was studied by Randomly Amplified Polymorphism DNA (RAPDs) and mitotic index on root tip cells. Differences between treated and control plants were observed in RAPD banding patterns as well as at the chromosomal level with a reduction of cell divisions. At cellular level we monitored the oxidative stress of treated plants in terms of reactive oxygen species (ROS) generation and ATP content. Again nCeO2 influenced clearly these two physiological parameters, while nTiO2 were ineffective. In particular, the dose 500 mg l-1 showed the highest increase regarding both ROS generation and ATP content; the phenomenon were detectable, at different extent, both at root and shoot level. Total Ce and Ti concentration in seedlings was detected by ICP-OES. TEM EDSX microanalysis demonstrated the presence of aggregates of nCeO2 and nTiO2 within root cells of barley. nCeO2 induced modifications in the chromatin aggregation mode in the nuclei of both root and shoot cells.